The Status of Selenium and Zinc in the Urine of Children From Endemic Areas of Kashin-Beck Disease Over Three Consecutive Years - Kang, Xin; Liu, Yanli; Gong, Yi; Huang, Lin; Liu, Hongliang; Hu, Minhan; Huang, Ruitian; Chen, Feihong; Chen, Sijie; Zhang, Feiyu; Ning, Yujie; Li, Cheng; et al. (Frontiers in Nutrition, 2022)
Selenium deficiency is a main risk factor for Kashin-Beck disease (KBD). This study aimed to detect the status of selenium and zinc in the urine of children from endemic areas of KBD over three consecutive years, and to evaluate whether selenium and zinc levels in children in Shaanxi Province remain normal after stopping selenium supplementation. The samples of urine were collected in consecutive years (2017-2019) to detect selenium content by hydride generation atomic fluorescence spectrometry (HGAFS) and to detect zinc content by atomic absorption spectrophotometry (AAS).. Generalized estimation equation (GEE) analysis was integrated to assess the comprehensive nutritional status and dietary structure of children. Data were processed in duplicate and analysed by SPSS 18.0. This study included 30 X-ray-positive KBD cases and 123 healthy children aged 7-12 years. A total of 424 urine and 137 hair samples were collected over three consecutive years for selenium determination. The mean value of urinary selenium in all subjects was 6.86 μg/l(2017), 8.26 μg/l(2018), 4.04 μg/l(2019) and the mean value of urinary zinc in all subjects was 0.36 mg/l(2017), 0.39 mg/l(2018), 0.31 mg/l(2019) for the three consecutive years of 2017-2019. The mean value of urinary selenium were 6.56 μg/l and 6.94 μg/l (2017), 8.69 μg/l and 8.14 μg/l(2018), 4.57 μg/l and 3.90 μg/l(2019) in the KBD-X and normal groups, respectively, and the mean value of urinary zinc were 0.38 mg/l and 0.35 mg/l(2017), 0.41 mg/l and 0.39 mg/l(2018), 0.43 mg/l and 0.28 mg/l(2019) in the KBD-X and normal groups, respectively. The mean value of hair selenium in 137 subjects was 275.08 μg/kg, and the mean values of hair selenium were 267.48 μg/kg and 276.61 μg/kg in the KBD-X group and normal group, respectively. The level of selenium/zinc showed a trend of increasing first and then decreasing during the three consecutive years. The level of selenium in all subjects from endemic areas was lower than normal, which reminds us to monitor the state of KBD constantly and adjust selenium salt supplementation in accordance with changes in KBD state.